MAPPADEKKO : STUDI ATAS TRADISI PESTA PANEN DI DESA BIALO KABUPATEN BULUKUMBA - Aulia, Guruh Ryan; Putri, Lindi Aulia (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2025)
This study explores the harvest festival tradition in Bialo Village, Bulukumba Regency, focusing on its origin, process, and cultural meaning. Using a qualitative approach through interviews, observation, and documentation, the research finds that the tradition stems from a local agricultural system emphasizing togetherness and gratitude. The festival includes collective prayers, traditional art performances, and shared meals of harvested crops. For the Bialo community, it is not merely a celebration but a cultural expression that fosters social cohesion and community identity. It also functions as a means to pass down local wisdom and values to younger generations. Amid ongoing modernization, the harvest festival plays a key role in preserving cultural identity and social resilience. It reflects the community's close connection with nature and reinforces the importance of sustaining traditional practices in an ever-changing cultural landscape.